2017
DOI: 10.3389/fphar.2017.00615
|View full text |Cite
|
Sign up to set email alerts
|

Using the Single Prolonged Stress Model to Examine the Pathophysiology of PTSD

Abstract: The endurance of memories of emotionally arousing events serves the adaptive role of minimizing future exposure to danger and reinforcing rewarding behaviors. However, following a traumatic event, a subset of individuals suffers from persistent pathological symptoms such as those seen in posttraumatic stress disorder (PTSD). Despite the availability of pharmacological treatments and evidence-based cognitive behavioral therapy, a considerable number of PTSD patients do not respond to the treatment, or show part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(81 citation statements)
references
References 92 publications
3
74
0
4
Order By: Relevance
“…Regarding fear symptoms, vulnerable rats showed intense freezing when exposed to SPS-related cues during a period extending from 29 to 54 days post-trauma. The robustness and persistence of these symptoms confirm the validity of SPS as a PTSD model 36,37 .…”
Section: Ptsd-like Behavioral Symptomssupporting
confidence: 58%
“…Regarding fear symptoms, vulnerable rats showed intense freezing when exposed to SPS-related cues during a period extending from 29 to 54 days post-trauma. The robustness and persistence of these symptoms confirm the validity of SPS as a PTSD model 36,37 .…”
Section: Ptsd-like Behavioral Symptomssupporting
confidence: 58%
“…20,21 For instance, SPS rats exhibit enhanced glucocorticoid negative feedback, 22 sleep abnormalities, 23 enhanced anxiety, 24-26 hyperarousal 27 and enhanced contextual freezing 28 as well as the expected therapeutic response to long-term treatment with paroxetine on enhanced fear memory. SPS mimics many aspects of the pathophysiological abnormalities associated with PTSD, and also some aspects of the behavioral characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…SPS mimics many aspects of the pathophysiological abnormalities associated with PTSD, and also some aspects of the behavioral characteristics. 20,21 For instance, SPS rats exhibit enhanced glucocorticoid negative feedback, 22 sleep abnormalities, 23 enhanced anxiety, [24][25][26] hyperarousal 27 and enhanced contextual freezing 28 as well as the expected therapeutic response to long-term treatment with paroxetine on enhanced fear memory. 29 Several studies have showed impaired fear extinction in SPS rats, 30,31 which is alleviated by repeated administration of D-cycloserine 32 or by single administration of vorinostat, a histone deacetylase inhibitor.…”
mentioning
confidence: 99%
“…Each SPS cohort began at 0800 h and ended with individual housing at 1300 h. Mice that were not randomized to SPS remained group housed for the duration of seven days that their counterparts underwent social isolation. Social isolation is a key component of SPS, and it has been shown to be a necessary incubation period for this trauma model [ 14 , 17 ].…”
Section: Methodsmentioning
confidence: 99%